2014
DOI: 10.4111/kju.2014.55.12.844
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency-Treated Recurrence of Urothelial Carcinoma of the Upper Urinary Tract After Nephroureterectomy

Abstract: Local recurrence after radical nephroureterectomy (RNU) owing to urothelial carcinoma of the upper urinary tract is rare. The usual treatment is systemic chemotherapy followed by optional resection of the mass. We introduce the case of a 73-year-old male patient with multiple comorbidities in whom retroperitoneal carcinoma recurrence of 31 mm was diagnosed via positron emission tomography-computed tomography scan with 18-fluorodeoxyglucose about 5 years after he had undergone RNU owing to urothelial carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…c W: Watt. summarised a total of 18 studies, which included 398 patients with 491 retroperitoneal tumours that were treated with thermal ablation, and showed that the ORR ranged from 74.5% to 100.0% [1][2][3][4][5][6][7][8][9][10][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…c W: Watt. summarised a total of 18 studies, which included 398 patients with 491 retroperitoneal tumours that were treated with thermal ablation, and showed that the ORR ranged from 74.5% to 100.0% [1][2][3][4][5][6][7][8][9][10][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Upper tract urothelial neoplasms account for approximately 10% of renal neoplasms and 5% of urothelial neoplasms (27). Patients with upper tract urothelial neoplasms are typically treated surgically, including nephroureterectomy and removal of a cuff of urinary bladder (28).…”
Section: Recurrent Urothelial Cancer-genitourinarymentioning
confidence: 99%